Ecofeminist Interconnections and Rebellion in Richard Powers’ The Overstory - Shrestha, Ravi Kumar (Historical Journal, 2025)
This paper investigates the exploitation and suppression of trees, drawing a parallel to the treatment of women, within Richard Powers' The Overstory. The novel underscores the critical global issue of ecological degradation, calling for urgent awareness and solutions. Powers critiques human ignorance and anthropocentrism, depicting both trees and humans as central figures to convey the message that trees, like humans, possess intrinsic value and agency. The portrayal of female characters in the novel closely mirrors nature, highlighting shared traits such as emotionality, care, altruism, empathy, compassion, and intuition. These qualities, make ecofeminism a fitting theoretical framework for textual analysis. Greta Gaard’s Ecofeminist theory states how the ideologies that enable the oppression of women, nature, and other marginalized groups are interconnected. This paper applies Gaard’s ecofeminist perspective to explore how The Overstory satirizes the human exploitation of nature and a parallel to the oppression of women. Employing a qualitative research methodology, this paper scrutinizes the interconnectedness of fictional human and non-human characters to examine the ecological destruction caused by the exploitation and subjugation of both nature and women.